Sosialisasi Pemanfaatan Mesin Pencacah dalam Pengelolaan Sampah Mendukung SDGs Desa Peswaran Indah - Prayitno, Hadi; Amrul; Irsyad, Muhammad; Nafrizal; Supono (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The purpose of this community service program in Desa Pesawaran Indah is to enhance public understanding and participation in sustainable waste management by introducing the 7R principles: Rethink, Refuse, Reduce, Repurpose, Reuse, Recycle, and Rot. Methodology: The program utilized a structured socialization approach, which included developing educational materials and conducting interactive discussions with village officials and members of the Women’s Farmers Group (KWT). Each 7R principle was introduced, practical applications were explored, and local waste management challenges were addressed. Results: The program resulted in a substantial increase in participants' understanding, with comprehension levels rising from an initial 2-4 participants to 18-21 participants who fully understood key principles like "Rethink" and "Recycle" by the program's conclusion. Conclusions: The program successfully enhanced community knowledge and engagement in sustainable waste management. Future initiatives could benefit from practical training to reinforce knowledge and empower participants to implement waste management strategies, contributing to the development of environmentally conscious communities aligned with broader sustainability goals. Limitations: The limitations of the study include the absence of practical demonstrations and the limited sample size, which may affect the generalizability of the findings. Contribution: This program contributes to the field of environmental education by promoting sustainable waste management practices within rural communities and aligning local actions with global sustainability goals.